2010
DOI: 10.1021/ac9027774
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid-Based Fluorescent Chiral Ionic Liquid for Enantiomeric Recognition

Abstract: We report on the synthesis and characterization of a new fluorescent chiral ionic liquid (FCIL), l-phenylalanine ethyl ester bis(trifluoromethane) sulfonimide (l-PheC(2)NTf(2)), capable of serving simultaneously as solvent, chiral selector, and fluorescent reporter in chiral analytical measurements. Enantiomers of different analytes, including fluorescent and nonfluorescent compounds, with a variety of structures were shown to induce wavelength- and analyte-dependent changes in the fluorescence intensity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 70 publications
0
34
0
Order By: Relevance
“…Recently, Bwambok et al used a simple metathesis reaction to synthesize some novel chiral ILs derived from amino acid esters . It was observed that l ‐alanine tert butyl ester bis(trifluromethane)sulfonamide ( l ‐AlaC 4 NTf 2 ), a room temperature IL, could serve as a chiral selector and a solvent . To the best of our knowledge, no studies have so far been performed on the enantioselective ability of the amino acid ester‐based ILs by use of any chromatographic or electrophoretic technique.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bwambok et al used a simple metathesis reaction to synthesize some novel chiral ILs derived from amino acid esters . It was observed that l ‐alanine tert butyl ester bis(trifluromethane)sulfonamide ( l ‐AlaC 4 NTf 2 ), a room temperature IL, could serve as a chiral selector and a solvent . To the best of our knowledge, no studies have so far been performed on the enantioselective ability of the amino acid ester‐based ILs by use of any chromatographic or electrophoretic technique.…”
Section: Introductionmentioning
confidence: 99%
“…Alanine-based and more recently a phenylalanine-based CIL were also synthesized in our laboratory and investigated for enantiomeric recognition. 25,50,51 The PCILs reported in this study are intrinsically fluorescent and could therefore also be used for probing nonfluorescent enantiomers by monitoring their intrinsic fluorescence intensities.…”
Section: Enantiomeric Recognition Of Chiral Analytes By Pcils Throughmentioning
confidence: 98%
“…In a recent report, Bwambok et al [76] originally synthesized a multifunctional IL, L-phenylalanine ethyl ester bis(trifluoromethane) sulfonimide (L-PheC 2 -NTf 2 ), to serve as solvent, chiral selector, and fluorescent report at the same time in chiral analytical measurements of different analytes including fluorescent and non-fluorescent compounds. Fig.…”
Section: Enantiomeric Separationsmentioning
confidence: 99%